2021
DOI: 10.1038/s41598-021-87990-6
|View full text |Cite
|
Sign up to set email alerts
|

Individuals with controlled hypertension show endothelial integrity following a bout of moderate-intensity exercise: randomized clinical trial

Abstract: To examine the acute effects of aerobic exercise (AE), resistance exercise (RE) or combined exercise (CE) on flow-mediated dilation (FMD), progenitor cells (PCs), endothelial progenitor cells (EPCs), oxidative stress markers and endothelial-cell derived microvesicles (EMVs) in patients with hypertension. This is a randomized, parallel-group clinical trial involving an intervention of one session of three different modalities of exercise. Thirty-three males (43 ± 2y) were randomly divided into three groups: a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…Proper physical exercise helps to raise the pulse rate and increase blood flow, which is beneficial to patients in a long-term ischemic state. The above discussion is consistent with recent research (Isabelle et al, 2016;Warnert et al, 2016;Campbell et al, 2019;Presa et al, 2020;Tofas et al, 2021;Waclawovsky et al, 2021).…”
Section: Heart Rate Pulse Rate and Blood Supplysupporting
confidence: 93%
“…Proper physical exercise helps to raise the pulse rate and increase blood flow, which is beneficial to patients in a long-term ischemic state. The above discussion is consistent with recent research (Isabelle et al, 2016;Warnert et al, 2016;Campbell et al, 2019;Presa et al, 2020;Tofas et al, 2021;Waclawovsky et al, 2021).…”
Section: Heart Rate Pulse Rate and Blood Supplysupporting
confidence: 93%
“…Several other studies identified challenges with recruitment and retention, citing low numbers of females as part of exercise programs or where clinical conditions are more common in males compared to females. Examples of these themes are illustrated in quotes in Figure 4 (Casey et al, 2007;Currie et al, 2012;Atkinson et al, 2015;Restaino et al, 2015; Paditsaeree and Mitranun, 2018;Santos-Parker et al, 2018;Claes et al, 2020;Papadakis et al, 2020;Boidin et al, 2021;Waclawovsky et al, 2021). In examining the identification of where generalizability is limited, studies primarily highlighted that because of the sex-specific nature of the study or the lack of equal participants across sex, study findings could not be generalized to other populations.…”
Section: Qualitative Analysis Of Study Reportingmentioning
confidence: 99%
“…Endothelial progenitor cells (EPCs) mobilized from bone marrow can migrate to the peripheral blood and differentiate into mature endothelial cells, contributing to endothelial recovery ( Pyšná et al, 2019 ). One study found that EPC number and activity was significantly reduced among people with hypertension when compared to healthy individuals, and low circulating levels of EPCs may contribute to endothelial dysfunction ( Waclawovsky et al, 2021 ). Abnormal circulating EMPs and EPCs in SHRs were ameliorated by berberine treatment associated with endothelial dysfunction and arterial stiffness in SHRs ( Zhang et al, 2020 ).…”
Section: Effects Of Berberine On Vascular Diseasesmentioning
confidence: 99%